Roots of nationhood the archaeology and history of Scotland - Campbell, Louisa; Wright, Dene; Hall, Nicola A. (Archaeopress archaeology., 2018)
In a break away from the traditional mono-disciplinary scope of academic enquiry, this volume sets forth a challenge for practitioners within, and outwith archaeology to develop multi-disciplinary approaches in the study of identity in general and aspects in the formation of national identity in particular. The entanglement of identity and nationhood is explored from the prehistory of northern Britain; the establishment of a proto-Scottish identity in the early Middle Ages; facets of Scottish identity at home and in the wider diaspora of Empire; and the more recent heralding of Scottish identity as a multiethnic construction. Set against the backdrop of a groundswell change in the Scottish political landscape and the unprecedented, and largely unexpected, energised and proactive politicisation of the Scottish electorate in the lead up to and aftermath of the 2014 Independence Referendum, the volume is a timely and relevant contribution to discussions of national identities. By bringing together specialists covering a wide array of time periods and subject specialisms, we transcend the concept of identity. This is achieved by exploring the links of nationhood and Scottish identity in the early 20th and 21st Centuries in the ongoing quest for independence demonstrating the political manipulation of history, imagery and mythology entangled in political propaganda.